Experimental Study on Seismic Performance of Kancingan Timber Frame Infill Walls Building - Sari Octavia; Hartawan Madeali; . Nasruddin; Mohammad Mochsen Sir (Salehan Institute of Higher Education, 2024)
This study was carried out to examine the seismic performance of Kancingan house walls and the behavior of their timber frames, brick infill, and anchor nails during cyclic loading tests. Kancingan House, a timber frame building with brick infill walls, is a cost-effective and efficient method of wall construction commonly used in houses in Merauke, Indonesia. The experimental method was used to determine the seismic performance of the walls built using buswood with a module width of 100 cm and a height of 130 cm through cyclic load testing. The result showed a maximum lateral load of 26.43 kN with a displacement of 19.08 mm under compression loading and 28.78 kN under tensile loading with 15.6 mm displacement. The initial stiffness was measured at 5.03 kN and 9.59 kN/mm for compressive and tensile loading, respectively. Furthermore, ultimate load and displacement of 21.14 kN and 23.02 kN were obtained at a displacement of 30.68 mm under compressive loading and 25.23 mm under tensile loading. The ductility values of 10.76 and 9.78 were obtained under compressive and tensile loading. In conclusion, the study found that each wall element supports the seismic performance of the structure. As opposed to the timber frame, the infill walls have not suffered much damage except a hair crack because of the presence of anchor nails that keep the infill wall from collapsing when it loses its bond with the timber frames. Doi: 10.28991/CEJ-2024-010-08-06 Full Text: PDF